Purification and characterization of the acyl carrier protein of the Streptomyces glaucescens tetracenomycin C polyketide synthase. - Shen, B (1992)
The acyl carrier protein (ACP) of the tetracenomycin C polyketide synthase, encoded by the tcmM gene, has been expressed in both Streptomyces glaucescens and Escherichia coli and purified to homogeneity. Expression of the tcmM gene in E. coli results mainly in the TcmM apo-ACP, whereas expression in S. glaucescens yields solely the holo-ACP. The purified holo-TcmM is active in a malonyl coenzyme A:ACP transacylase assay and is labeled by radioactive beta-alanine, confirming that it carries a 4'-phosphopantetheine prosthetic group.